MANAJEMEN PEMBELAJARAN PENDIDIKAN AL ISLAM DALAM KURIKULUM MERDEKA BELAJAR - Badriyah , Nurul; Istikomah, Istikomah (PAI RAFAH, 2024)
This research aims to determine the learning management of Al-Islam education in the independent curriculum at SMP Muhammadiyah 5 Tulangan. This type of research is qualitative with a descriptive approach, research data in the form of teaching modules, lesson plans and syllabi. The data sources for this research were obtained from informants or observations and interviews involving school principals, curriculum leaders, and Al-Islam education teachers. The independent curriculum is a curriculum initiated by the Minister of Education and Culture (Kemendikbud), Nadiem Makarim, which gives freedom to educational units in designing and implementing learning according to the characteristics and needs of students. The learning management of Al-Islam education at SMP Muhammadiyah 5 Tulangan has been carried out in accordance with predetermined learning procedures and is running well in accordance with the predetermined learning objectives. In carrying out learning, the teacher will deliver teaching materials in 3 stages starting from introductory activities, core activities and closing activities. The learning approach uses differentiation by strengthening the Pancasila student profile.